2019
DOI: 10.1165/rcmb.2018-0328oc
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Regulates the Onset of Oxidant-induced Senescence in Lung Fibroblasts

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease of unknown cause with a median survival of only 3 years. We and others have shown that fibroblasts derived from IPF-lungs display characteristics of senescent cells and that dysregulated activation of the transcription factor signal transducer and activator of transcription 3 (STAT3) correlates with IPF progression. The question of whether STAT3 activation is involved in fibroblast senescence remains unanswered. We hypothesized that inhibiting STAT3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…Senescent fibroblasts that display respiratory abnormalities, indicating mitochondrial damage, express both STAT3 and p21 as markers of the senescent phenotype [30]. MIA-602 downregulates p21-activated kinase and STAT3 and NFκB in gastric cancer cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…Senescent fibroblasts that display respiratory abnormalities, indicating mitochondrial damage, express both STAT3 and p21 as markers of the senescent phenotype [30]. MIA-602 downregulates p21-activated kinase and STAT3 and NFκB in gastric cancer cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fibroblast senescence on the pathobiology of asthma is not clear yet, but we could still find some clues. Some investigators have demonstrated that the activation of transcription factor signal transducer and activator of transcription 3 (STAT3) might contribute to lung fibroblast senescence in patients with IPF (Waters et al, 2018(Waters et al, , 2019.…”
Section: Mesenchymal Cell Senescencementioning
confidence: 99%
“…Thus, GHRH-R antagonists regulate the AMPK pathway and growth in lung cells. Pulmonary artery endothelial cells likewise respond to inhibition of the GHRH-R by the downregulation of extracellular signal related kinase (ERK1/2) and Janus kinase-signal transducer and activator of transcription (JAK2/STAT3) pathways, which are implicated in both lung inflammation and apoptosis [ 18 , 19 ].…”
Section: Ghrh In the Lungmentioning
confidence: 99%